Politics, religion and revolution in Jeffrey Klaiber S. J.’s early work on Peru - Portocarrero Grados, Ricardo Felipe (2020)
The objective of this article is to study the historical context and the political and intellectual process of the first research works carried out by the North American historian Jeffrey Klaiber S. J. In his works, he focused on the possibilities of a profound change in Peru through reformist policies, which found in the Peruvian Aprista Party its main political actor. In addition, he studied the relationships between the reformist elites and the popular sectors throughout our republican history, the main result of which was his important book Religion and Revolution in Peru, 1824-1988.